2001
DOI: 10.1086/501879
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Frequency of Changing Intravenous Administration Sets: Is It Safe to Prolong Use Beyond 72 Hours?

Abstract: In patients at low risk for infection from infusion- or catheter-related infection who are not receiving total parenteral nutrition, blood transfusions, or interleukin-2, delaying the replacement of IV tubing up to 7 days may be safe, as well as cost-effective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 16 publications
2
53
1
6
Order By: Relevance
“…Data from a more recent study demonstrated that rates of phlebitis were not substantially different if administration sets were left in place 96 hours compared with 72 hours [128]. When a fluid that enhances microbial growth is infused (e.g., lipid emulsions and blood products), more frequent changes of administration sets are indicated, because these products have been identified as independent risk factors for CRBSI [152][153][154][155][156][157][158].…”
Section: Replacement Of Administration Setsmentioning
confidence: 99%
“…Data from a more recent study demonstrated that rates of phlebitis were not substantially different if administration sets were left in place 96 hours compared with 72 hours [128]. When a fluid that enhances microbial growth is infused (e.g., lipid emulsions and blood products), more frequent changes of administration sets are indicated, because these products have been identified as independent risk factors for CRBSI [152][153][154][155][156][157][158].…”
Section: Replacement Of Administration Setsmentioning
confidence: 99%
“…CLABSIs are an independent risk factor for increased hospital costs and length of stay. There are four recognized routes for contamination of CVCs: (i) migration of organisms colonizing the skin at the insertion site into the catheter tract, along the catheter surface, and consequently colonization of the catheter tip (2-4); (ii) direct contamination of the catheter/catheter hub through contact with hands, contaminated fluids, or contaminated devices (5, 6); (iii) hematogenous seeding from another focus of infection (7); and (iv) rarely, contamination of intravenous infusate solutions (8). The microorganisms most commonly associated with CVC infection are Staphylococcus aureus (including methicillin-resistant S. aureus [MRSA]) and coagulase-negative staphylococci (CoNS) (9)(10)(11).…”
mentioning
confidence: 99%
“…The risk of catheter-related infection correlates with the patient's age, weight, underlying diseases, immune system status and type of fluid injection (15,16). Several preventive techniques have been shown, which can reduce the incidence of infections including: adequate knowledge, insertion and keeping of catheter only in necessary situations, hygiene, use of appropriate solutions (alcoholicchlorhexidine) for skin disinfection, care protocol implementation, CVC insertion under ultrasound guidance, preference of subclavian line instead of other sites, change of dressings (no more than seven days), and avoiding antibiotic prophylaxis (1,(17)(18)(19)(20). The most important principle of prevention is personnel training for catheter care and observing the principles of sterilization (15,21).…”
Section: Discussionmentioning
confidence: 99%